Pemberdayaan Ibu PKK melalui Diversifikasi Pangan Lokal Berbasis Sagu di Desa Mata Lamokula Kabupaten Konawe Selatan - Asniar,; Wa Anasari,; Misdayanti,; Maulidiyah,; Tamrin,; Herdiansyah, Dhian; Ansharullah, (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to improve nutritional knowledge, develop practical skills in producing sago–moringa–cheese cookies among members of the Family Welfare Empowerment (PKK) group, and promote the diversification of economically valuable local food products to support stunting prevention efforts in Mata Lamokula Village. The program was implemented using a participatory approach that included educational sessions and demonstrations. Participants' practical skills were evaluated using an observation checklist, and the data were analyzed descriptively. The results showed that all participants successfully prepared three varieties of sago cookies in accordance with the demonstrated procedures. Participants also demonstrated increased awareness of the importance of utilizing local food resources to improve family nutrition. Furthermore, the program strengthened participants' economic motivation and enhanced collaboration among PKK members in developing local food-based enterprises.